The Southern African Program on Ecosystem Change and Society: an emergent community of practice. Issue 1 (31st December 2023) - Biggs, Reinette (Oonsie); Reyers, Belinda; Blanchard, Ryan; Clements, Hayley; Cockburn, Jessica; Cumming, Graeme S.; Cundill, Georgina; de Vos, Alta; Dziba, Luthando; Esler, Karen J.; Fabricius, Christo; Hamann, Maike; et al.
ABSTRACT: Sustainability-focused research networks and communities of practice have emerged as a key response and strategy to build capacity and knowledge to support transformation towards more sustainable, just and equitable futures. This paper synthesises insights from the development of a community of practice on social-ecological systems (SES) research in southern Africa over the past decade, linked to the international Programme on Ecosystem Change and Society (PECS). This community consists of a network of researchers who carry out place-based SES research in the southern African region. They interact through various cross-cutting working groups and also host a variety of public colloquia and student and practitioner training events. Known as the Southern African Program on Ecosystem Change and Society (SAPECS), its core objectives are to: (1) derive new approaches and empirical insights on SES dynamics in the southern African context; (2) have a tangible impact by mainstreaming knowledge into policy and practice; and (3) grow the community of practice engaged in SES research and governance, including researchers, students and practitioners. This paper reflects on experiences in building the SAPECS community, with the aim of supporting the development of similar networks elsewhere in the world, particularly in the Global South.